2015
DOI: 10.1007/s12038-015-9567-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory single nucleotide polymorphisms at the beginning of intron 2 of the human KRAS gene

Abstract: There are two regulatory single nucleotide polymorphisms (rSNPs) at the beginning of the second intron of the mouse K-ras gene that are strongly associated with lung cancer susceptibility. We performed functional analysis of three SNPs (rs12228277: T greater than A, rs12226937: G greater than A, and rs61761074: T greater than G) located in the same region of human KRAS. We found that rs12228277 and rs61761074 result in differential binding patterns of lung nuclear proteins to oligonucleotide probes correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Other studies have shown that intronic SNPs can impact enhancer activity and splicing, which can result in altered mRNA and protein expression and can change the characteristics of those genes (Wang et al, 2014;Wang and Sadee, 2016;Schwartz et al, 2017). Intergenic SNPs have also been observed to impact enhancer activity and the binding of transcription factors (Flora et al, 2013;Spasovski et al, 2013;Antontseva et al, 2015;Schierding et al, 2016). Thus, the intronic and intergenic SNPs we have identified could be impacting biomarker levels after isocyanate exposure by acting as modifiers of gene regulation and transcription.…”
Section: Bioinformaticsmentioning
confidence: 63%
“…Other studies have shown that intronic SNPs can impact enhancer activity and splicing, which can result in altered mRNA and protein expression and can change the characteristics of those genes (Wang et al, 2014;Wang and Sadee, 2016;Schwartz et al, 2017). Intergenic SNPs have also been observed to impact enhancer activity and the binding of transcription factors (Flora et al, 2013;Spasovski et al, 2013;Antontseva et al, 2015;Schierding et al, 2016). Thus, the intronic and intergenic SNPs we have identified could be impacting biomarker levels after isocyanate exposure by acting as modifiers of gene regulation and transcription.…”
Section: Bioinformaticsmentioning
confidence: 63%
“…Besides, we analysed two SNPs from promoter 1B (rs115658307: C > T and rs78429131: T > G) that did not change the protein binding pattern, because it is known that substitutions that do not affect the binding of nuclear-extract proteins can nevertheless influence the expression of a reporter [22]. …”
Section: Resultsmentioning
confidence: 99%
“…These differences represented either an increase or decrease in the affinity of some TFs, or even disappearance or appearance of binding sites for TFs. Such alterations in TF binding patterns can strongly influence gene expression [22, 3436]. Indeed, the luciferase reporter assay suggested that all four analyzed SNPs (which demonstrated differential binding patterns in the EMSA) were functionally active.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the somatic mutation theory, the key point in cancer transformation is DNA damage, e.g., due to aberrantly regulated or nonfunctional DNA repair pathways [3]. Cancer cells accumulate mutations several times faster than the normal cells [4]. It contributes to deregulation of molecular pathways including those responsible for apoptosis, cell growth, metabolism, motility and immunosuppression [5,6].…”
Section: Introductionmentioning
confidence: 99%